Efficacy of shared decision making in tobacco cessation among health facilities of Haryana, India – A double blinded, parallel group Randomized Controlled trial Protocol - Pranav Kshtriya; Sonu Goel; Abhishek Ghosh (Public Health in Practice)
Background: Shared decision-making (SDM) incorporates evidence, patient values, and preferences into medical decision-making. SDM and decision aids might promote health professional engagement and patient knowledge of tobacco cessation therapy, improving usage and results. The SDM facilitates talks that lead to better-informed judgements that align with patients' priorities, unlike individual decision-making. Thus, the study will attempt to identify the efficacy of shared decision making in tobacco dependence treatment. Methods: 1) Design: a two-arm parallel group randomized controlled trial (RCT) 2) Setting: Three selected government health centers of Haryana, India. 3) Participants: 596 tobacco users aged ≥18 visiting the outpatient department/Tobacco cessation centers (TCC) of selected health centers. 4) Intervention and Comparator: The intervention group will receive shared decision process for prescribing pharmacotherapy (Nicotine replacement therapy, Bupropion) using specially designed decision aid based on three-talk model for tobacco cessation, while the control group will get standard care. 5) Measurements: Primary outcomes include urinary cotinine analysis for evaluating 7-day point prevalence abstinence. Secondary outcomes include patient satisfaction questionnaire PSQ-18 score, cumulative days of tobacco abstinence, self-reported number of quit attempts, and the rate of withdrawal. The outcomes such as change in behavior status i.e. tobacco cessation will be compared between the intervention and the comparator groups. When comparing the two groups, differences between proportions will be assessed by chi-square test, differences between means with t-test. An intention to treat analysis will be done when comparing outcomes in both arms. Discussion: SDM in tobacco cessation therapies in healthcare settings is understudied, thereby this study looks at comparable interventions in different settings to add to the evidence. This suggests that this study on SDM in tobacco cessation therapy, which includes healthcare professionals, aims to assist patients in making evidence- and value-based medical decisions. Trial registration: This protocol has been registered under the registration number CTRI/2022/10/046793 with the Clinical Trials Registry in India.